The GCM domain is a Zn-coordinating DNA-binding domain - Wegner, Michael; et al. (Febs Letters, 2002)
Glial cells missing (GCM) proteins form a small family of transcriptional regulators involved in different developmental processes. They contain a DNA-binding domain that is highly conserved from flies to mice and humans and consists of approximately 150 residues. The GCM domain of the mouse GCM homolog a was expressed in bacteria. Extended X-ray absorption fine structure and particle-induced X-ray emission analysis techniques showed the presence of two Zn atoms with four-fold coordination and cysteine/histidine residues as ligands. Zn atoms can be removed from the GCM domain by the Zn chelator phenanthroline only under denaturating conditions. This suggests that the Zn ions are buried in the interior of the GCM domain and that their removal abolishes DNA-binding because it impairs the structure of the GCM domain. Our results define the GCM domain as a new type of Zn-coordinating, sequence-specific DNA-binding domain. © 2002 Federation of European Biochemical Societies. Published by Elsevier Science B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2002.med.IB.LPCIPDBI.thegcm
Keywords: DNA-binding domain; EXAFS; Transcription factor; Zn coordination